2021
DOI: 10.1111/1462-2920.15720
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation is associated with differences in facilitative and competitive interactions in the Rhizobium leguminosarum species complex

Abstract: Competitive and facilitative interactions influence bacterial community composition, diversity and functioning. However, the role of genetic diversity for determining interactions between coexisting strains of the same, or closely related, species remains poorly understood. Here, we investigated the type (facilitative/inhibitory) and potential underlying mechanisms of pairwise interactions between 24 genetically diverse bacterial strains belonging to three genospecies (gsA,C,E) of the Rhizobium leguminosarum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 134 publications
(239 reference statements)
2
6
0
Order By: Relevance
“…In support of this hypothesis, we found that gsB strains displayed relatively highest maximum growth rates and biofilm formation in TY broth, which could have helped them to establish symbiosis more frequently compared to other genospecies strains (Figure S9). These competitive differences are in line with our previous study where we showed that R. leguminosarum genospecies A, C and E display clear differences in competitive fitness and metabolic capacities, despite not differing in their symbiotic performance on white clover (Fields, Moffat, Friman, & Harrison, 2021; Fields, Moffat, Harrison, et al, 2021). However, as gsB strains did not dominate across all varieties and crosses, it is possible that changes in genospecies frequencies were also driven by host preference for compatible symbionts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of this hypothesis, we found that gsB strains displayed relatively highest maximum growth rates and biofilm formation in TY broth, which could have helped them to establish symbiosis more frequently compared to other genospecies strains (Figure S9). These competitive differences are in line with our previous study where we showed that R. leguminosarum genospecies A, C and E display clear differences in competitive fitness and metabolic capacities, despite not differing in their symbiotic performance on white clover (Fields, Moffat, Friman, & Harrison, 2021; Fields, Moffat, Harrison, et al, 2021). However, as gsB strains did not dominate across all varieties and crosses, it is possible that changes in genospecies frequencies were also driven by host preference for compatible symbionts.…”
Section: Discussionsupporting
confidence: 91%
“…As several molecular selection processes are involved in Rlt x clover genotype compatibility and partner choice, future work should investigate the mechanisms of symbiotic selectivity, such as the importance of extracellular polysaccharides, secretion system specificity and microbe‐associated molecular pattern detection by the legume host to consider how these factors may affect the success of both host and symbiont (Perret et al, 2000; Simms & Taylor, 2002; Wang, Liu, & Zhu, 2018). Our previous work has also shown that different Rlt genospecies can be highly competitive through resource competition and direct antagonism likely via bacteriocins and quorum‐sensing associated mechanisms (Fields, Moffat, Harrison, et al, 2021), which could also partly explain the dominance of gsB strains. Finally, it has previously been shown that legume–rhizobium symbiotic compatibility can evolve rapidly over five plant generations (Batstone et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…They identified 72 isolates, which based on a concatenated sequence of 305 conserved core genes and ANI (Average Nucleotide Identity) parameter were sufficiently diverged to be recognized as separate genospecies (named as gsA-E). Interestingly, different effects of interactions between these strains were detected (growth stimulation or suppression), depending on their genospecies (e.g., gsE showed the highest inhibition capacity, whereas gsA the highest susceptibility) 64 . Moreover, Young and others showed that three house-keeping gene sequences ( atpD , gyrB , and recA ) are sufficient to assign strains to individual genospecies 57 .…”
Section: Discussionmentioning
confidence: 99%
“…We do not yet have a clear understanding of the interplay of genetic and ecological processes that lead to the creation and maintenance of well-defined but closely related bacterial species in a species complex such as the Rlc. An intriguing first indication of ecological differences between species in the Rlc is provided by a recent study of pairwise strain interactions that showed, for example, that gsA strains were inhibited by medium in which gsE strains have grown, but growth enhancement was seen in the reciprocal experiment [22]. There is much more to do, but an important first step is to provide a clear definition of the species involved.…”
Section: Evidence For the Novel Speciesmentioning
confidence: 99%